Effects of a physiological exercise test and a HIIT shock microcycle on muscle fatigue measured with a novel device - case study on acute and chronic changes - Strepp, T.; Blumkaitis, J.; Haller, N.; Stöggl, T. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: The importance of managing fatigue has led to an increased interest in finding practicable and objective measures to quantify fatigue 1. A recent study introduced the Myocene device to measure muscle fatigue (MF) based on the force generated by electrical muscle stimulation. Results demonstrated valid measurements of MF after a strenuous series of drop jumps 2. However, there is no data on the effects of a physiological exercise test (PET) or repeated HIIT sessions in form of a shock microcycle (HIIT-SM). HIIT-SM are commonly used in winter sports to efficiently stimulate the aerobic system in short preparation periods and to spend more time on on-snow training 3. The aim of this study was to monitor acute responses of MF induced by a PET and chronic MF changes during a HIIT-SM using the Myocene device.